Cardiac magnetic resonance imaging in myocardial inflammation in autoimmune rheumatic diseases: An appraisal of the diagnostic strengths and limitations of the Lake Louise criteria. (1st February 2018) - Mavrogeni, Sophie; Schwitter, Juerg; van Rossum, Albert; Nijveldt, Robin; Aletras, Antony; Kolovou, Genovefa; Pohost, Gerald; Lima, Joao
Abstract: Myocardial inflammation in autoimmune rheumatic diseases (ARDs) is the endpoint of various pathophysiologic processes. The Lake Louise-criteria is the most popular approach for the diagnosis of myocarditis. However, due to the diversity of myocardial inflammation in ARDs, some issues should be acknowledged. Of the three Lake Louise indices, early and late gadolinium enhancement (EGE and LGE respectively) measurements may be affected by co-existing disease processes or be present due to a fibrotic ARD like systemic sclerosis, leaving T2-ratio as the only uniformly robust measurement across ARDs. It thus becomes apparent that the Lake Louise criteria suffer from a number of limitations when ARD patients are assessed based on them. The introduction of T1/T2 mapping allowed the quantification of intramyocardial fibrosis missed by LGE and the detection of myocardial oedema respectively, both commonly found in ARDs. The Lake Louise criteria play an important role in the evaluation of AIMI in ARDs. However, the pathophysiologic background of cardiac involvement in ARDs should always be acknowledged in their evaluation. Even though the inclusion of T1/T2 mapping and ECV may better describe diffuse oedema and fibrosis, further investigation pertaining to their implementation in ARD assessment algorithms through multicenter studies is needed.